Gentle revolutionary : the life of St. Francis of Assisi - Daughters of St. Paul. (Boston : St. Paul Editions, 1978)
Recounts the life of St. Francis of Assisi who gave up his wealth in order to devote his life to serving and teaching the poor.
Keywords: Francis, -- of Assisi, Saint, -- 1182-1226 -- Juvenile literature; Francis, -- of Assisi, Saint, -- 1182-1226.; Christian saints -- Italy -- Assisi -- Biography -- Juvenile literature; Saints; Assisi (Italy) -- Biography -- Juvenile literature